Essential Paediatrics and Child Health - Rudolf, Mary; Luder, Anthony; Jeavons, Kerry (West Sussex, UK : WILEY Blackwell, 2020)
Essential Paediatrics and Child Health is a comprehensive and practical guide to paediatric disorders as they present to the student and practitioner, offering step-by-step guidance on symptom assessment, history taking, physical examination, investigation and diagnosis, management and treatment, patient education, follow-up and prognosis. With full-colour images and a range of unique and innovative learning features, this completely revised new edition of the award-winning book Paediatrics and Child Health will prove an invaluable resource for medical students and junior doctors on their journey through contemporary paediatrics.
Includes index.
Includes questions and exercises.
Keywords: Pediatrics; Child Welfare